Effectiveness of Video Assisted Teaching (VAT) on Jacobson Progressive Muscle Relaxation (JPMR) Exercises to Reduce the Stress Level among B.Sc. Nursing Students - Deepak Kumar Shandily; Tapti Bhattacharjee; Ramandeep Kaur Dhillon (Indian Journal of Forensic Medicine & Toxicology, 2021)
Stress is the mileage that life causes on the body. Every individual is facing one or another stressful events inlife, in which students are also not an exception. Present study aimed to examine the effectiveness of JacobsonProgressive Muscle Relaxation (JPMR) Exercises to Reduce the Stress Level among B.Sc. Nursing Studentsat selected nursing institutes of Punjab and Haryana State. This was a pre-experimental one group pre-testand post-test study, in which 500 B.Sc. Nursing students were recruited by using non-probability convenientsampling technique. The study tools socio-demographic variables and Modified Perceived Stress Scale(MPSS) was used to gather the information’s. After pre-test the JPMR were introduced to each participantthrough video-assisted teaching and after 7th day of JPMR the post-test conducted. Analysis of study notedthat majority of participants 51.2% have shown that they don’t have previous knowledge about JPMR, whilehighest number of participants 50% reported that they have once seen JPMR but not performed ever. Thepaired t test value of total academic score was 213.518 at calculated p value of <0.001 which concluded thatthe administered JPMR is effective to reduce the stress level among B.Sc. Nursing students.